Enhancing Local Economic Impact - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance on how to ensure that an agricultural investment generates positive impacts on the local economy by encouraging and supporting opportunities arising for individuals, farmers, businesses, and institutions. Investments can have a transformative impact on the communities where they are located. Much of this impact can be long term, and go beyond the immediate activities of the investors, through economic linkages and spillover effects. Positive impacts on the local economy are not automatic: the policies and practices of the investor and the government influence outcomes. Careful management and choice of agricultural investments, and provision of complementary initiatives by investors and by governments, can maximize the benefits arising from economic linkages and spillovers while minimizing the risks.